Representative dual-energy CT and PET images in patients with lymph node metastasis. - Xuyang Sun (7146668) (2024)
Contrast-enhanced CT image (a), iodine map (b), and PET image (c) of an 83-year-old man with esophageal cancer; images show swelling of the right supraclavicular lymph node (a, b, c arrows), which was confirmed as metastasis postoperatively. The low iodine concentration (1.45 mg/mL) and high maximal standardized uptake value (10.7) were measured. CT: computed tomography; PET: positron-emission tomography.